2014
DOI: 10.4103/2249-4847.134691
|View full text |Cite
|
Sign up to set email alerts
|

The main etiologies of acute Kidney injury in the newborns hospitalized in the neonatal intensive care unit

Abstract: Introduction:Acute kidney injury (AKI) is one of the most common diseases among the newborns hospitalized in the neonatal intensive care units (NICUs), which is usually resulted from predisposing factors including sepsis, hypovolemia, asphyxia, respiratory distress syndrome (RDS), and heart failure. The goal of this study was to assess main etiologies, relevant risk factors, and early outcome of neonatal AKI.Materials and Methods:In a cross- sectional study, 49 consecutive neonates hospitalized in NICU of Besa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 11 publications
3
22
1
2
Order By: Relevance
“…Gharehbaghi et al 17 from Iran also reported male to female ratio was 2.03:1 (67% versus 33%) showing same trends as that of our study results. Similar results have been reported by Airede et al 18 Kandoth et al 19 and Bourquia et al 20 However Momtaz et al 21 have reported different findings showing female gender predominating among newborns with AKI. Acute renal failure is generally observed in first few days of life to couple of weeks time.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Gharehbaghi et al 17 from Iran also reported male to female ratio was 2.03:1 (67% versus 33%) showing same trends as that of our study results. Similar results have been reported by Airede et al 18 Kandoth et al 19 and Bourquia et al 20 However Momtaz et al 21 have reported different findings showing female gender predominating among newborns with AKI. Acute renal failure is generally observed in first few days of life to couple of weeks time.…”
Section: Discussionsupporting
confidence: 84%
“…Gharehbaghi et al 17 from Iran also reported 5.26 ± 6.2 days ranging from 2–28 days. Similarly, Momtaz et al 21 reported 7.7 ± 6.3 days mean age in newborns with AKI. Mean weight of these neonates was 2545.05 ± 600.42 grams (range; 1000 grams to 4000 grams).…”
Section: Discussionmentioning
confidence: 79%
“…Congenital abnormalities of kidney and genital-urinary tract are also reported to contribute to AKI among neonates [16]. In our findings, 29 out of 74 participants with AKI who had KUB ultrasound scans had congenital abnormalities of the genitourinary system detected only by ultrasound.…”
Section: Discussionsupporting
confidence: 50%
“…Neonatal AKI may result in devastating outcomes including prolonged hospital stays, chronic kidney disease, end stage renal failure and deaths. [5,14,16,21,22]. Mortality as high as 73% was reported for children with AKI in a systematic review of AKI in sub-Saharan Africa [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, about 15% of patients died and 85% were discharged. Overall, the predisposing factors include underlying etiology, female gender, birth asphyxia, low birth weight, multiorgan failure, hypotension, septicemia, profound acidosis, shock, oligoanuria, nephrotoxic drugs, vasopressor treatment, mechanical ventilation, and peritoneal dialysis (13,15).…”
Section: Serum Phmentioning
confidence: 99%